2022
DOI: 10.3390/chemengineering6030034
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bioactive Sauce: Effect of the Packaging and Storage Conditions

Abstract: Consumers’ interest in a high-quality healthy diet is creating a growing trend in the food industry, focusing on the design and development of new products rich in bioactive compounds. This work involves the formulation of a vegetable sauce obtained from a mixture of pumpkin and pepper, the study of the evolution of bioactive compounds, quality and sensory parameters during storage at 4 and 25 °C, the influence of the packaging materials (PVC, PE/PA, and PS), and the migration degree. Antioxidant activity, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Natural products with dual efficiency as antimicrobial properties and preventing lipid oxidation have incredible potential for extending the shelf life of food products. Essential oil from the fruit pulp of F. limonia can be considered as a new and potential source of natural antimicrobial agent and antioxidant [15][16][17][18].…”
Section: Effect Of Storage On Organoleptic Evaluation Of the Develope...mentioning
confidence: 99%
“…Natural products with dual efficiency as antimicrobial properties and preventing lipid oxidation have incredible potential for extending the shelf life of food products. Essential oil from the fruit pulp of F. limonia can be considered as a new and potential source of natural antimicrobial agent and antioxidant [15][16][17][18].…”
Section: Effect Of Storage On Organoleptic Evaluation Of the Develope...mentioning
confidence: 99%
“…There are some studies reporting the presence of plastic particles (nano, micro, meso, and/or macro plastic) in seafood and fish for human consumption (Alak et al., 2021; Barboza et al., 2020; Cox et al., 2019; Karami et al., 2018). Some studies had shown that fishery products contaminated with MPs are transferred to the upper levels of the food chain and consumed by humans (Braeuning, 2019; Eriksson & Burton, 2003; Giménez et al., 2022; Nalbone et al., 2021; Zarfl et al., 2011). However, the relationship between the feeding types of fish (swallowing, filter feeding, sucking, etc.)…”
Section: Introductionmentioning
confidence: 99%